Quality of fresh milk before normative instruction IN 76 of the Ministry of Agriculture, Livestock and Supply of Brazil (Research, Society and Development, 2020)
Due to the quality, of the milk, being defined by its physical-chemical and microbiological parameters, normative instruction n ° 76 was established that recommends the mandatory requirements to the producer. The objective of this work was to evaluate the refrigerated fresh milk from four rural properties in the municipality of Rio Verde - GO, regarding the presence of psychrotrophic and proteolytic psychrotrophic microorganisms together with the CBT, CCS and proximal composition of the milk comparing the results with the required by IN 76. The samples of chilled raw milk were collected and later, the milk samples for CBT and CCS analysis, were sent for diagnosis at the Milk Quality Laboratory of the School of Veterinary Medicine and Zootechnics of the Research Center in Food at the Federal University of Goiás (LQL). Milkoscan 4000 equipment (Foss Electric A / S. Hillerod, Denmark) was used to determine the levels of fat, protein, lactose, total dry extract (EST), (ESD), urea and casein. Standard counts were performed on viable proteolytic psychrotrophic and psychrotrophic microorganism plates and the number of CFU / mL of the sample was calculated by multiplying the number of colonies on each plate by the inverse of the dilution. Results were obtained from the values of CBT, CCS, proximal composition, urea, casein, psychrotrophic and proteolytic psychrotrophic microorganisms that are mostly satisfactory and within the limits of the legislation, demonstrating the concern with good hygiene, handling and health practices of the animals that the owners of rural properties have.